ANALISIS HUKUM KOMERSIALISASI PATEN MELALUI INTELLECTUAL PROPERTY MARKETPLACE MENURUT HUKUM POSITIF INDONESIA - Permana, Yoga (JIPRO: Journal of Intellectual Property, 2025)
The fairly active invention discovery activity in Indonesia for a period of almost three decades requires a mechanism that allows patents to be utilized optimally, not only by their owners but also by other parties through commercialization channels such as the provision of an intellectual property marketplace system. This system supports collaboration between inventors and patent holders which is very important to ensure that the economic potential of patents can be fully realized. The research was conducted using a normative legal approach using secondary data. The data collection technique was carried out using a literature study that was analyzed qualitatively. Legal protection is important in the Intellectual Property commercialization ecosystem to accommodate and legitimize the existence of an intellectual property marketplace. Several regulations such as PP No. 24/2022, the Patent Law, and the ITE Law are the basis for the intellectual property marketplace. Infrastructure development in patent commercialization will help bridge the gap between the creation and commercialization of intellectual property rights, so various components of development in patent commercialization need to be realized such as an intellectual property valuation system, contract standardization, and an inventory of intellectual property rights.